High Visible Response of Vertical TiO2 Nanoclusters-CdSe Linked by Cysteine - Fang Zhou, Fu; Li, Delong; Wu, Wenhui; Zhao, Liuying; Wang, Ping; Ming Huang, Yuan; Pan, Chunxu (Asian Journal of Chemistry, 2014)
Vertically oriented single-crystal TiO2 nanoclusters in tetramethylammonium hydroxide solution were synthesized hydrothermally directly on Ti substrate. N-Type semiconducting CdSe nanoparticles were then introduced deep coating TiO2 nanocrystalss via a two-step procedure using cystein as a surface coupling agent, followed by a subsequent electrodeposition process from selenosulfite to form orderly interconnecting heterojunctions. A key result achievement is that although the TiO2nanocrystalss are less than 1 μm long, under the help of the bifunctional 2-amino-3-sulfhydrylpropanoic acid molecule linking the acceptor and donor materials, the virtue of strong visible absorption of single crystal TiO2 nanoclusters were fully developed in addition of ultraviolet, so that the heterojunction electrode exhibits excellent photoresponse in photoelectrochemical cells to visible lights, whose contribution is rather significant compared with that of ultraviolet lights. Vertical nanoclusters have advantages of leading electrons directly into the metal Ti substrate while maintaining the large surface area towards the electrolyte. These highly ordered nanohybrids are expected to have potential applications in photochemical solar cells with high efficiency.